Literatura ukraińska i jej ekranizacje w nauczaniu języka ukraińskiego i kultury ukraińskiej jako obcych ......... 161 - Zbyr, Iryna (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
UKRAINIAN LITERATURE AND ITS FILM ADAPTATIONS IN TEACHING THE UKRAINIAN LANGUAGE AND CULTURE AS FOREIGNThe proposed article discusses the problem of teaching Ukrainian literature in the curriculum of Ukrainian Language and Culture to Foreigners, views on this topic, and the author’s proposals to find a solution, based on her own experience and the challenges of the time. The article contains rich illustrative material from classes devoted to Ukrainian Literature to Foreigners. This article aims to show the role and place of literary texts in teaching Ukrainian as a foreign language and to describe the main techniques of teaching Ukrainian literature based on the author’s own experience, in particular the use of film adaptations in studying Ukrainian literature and culture by foreign students.